Spatial nonuniform distribution of ²³⁵U isotope at supercritical fluid extraction with carbon dioxide in a gradient temperature field - Borts, B.V.; Skoromnaya, S.F.; Kazarinov, Yu.G.; Neklyudov, I.M.; Tkachenko, V.I. (Вопросы атомной науки и техники, 2021)
The spatial redistribution of the ²³⁵U isotope of natural uranium in a gradient temperature field along the height of the reactor in supercritical carbon dioxide has been experimentally investigated. The scheme of the reactor is given and the principle of operation of the reactor is described. The method of preparation of initial samples from granite samples containing natural uranium and the procedure of extraction are described. The conclusion about the spatial redistribution of ²³⁵U isotopes in supercritical carbon dioxide is based on the analysis of gamma spectra of extracts. It is shown that the concentration of the ²³⁵U isotope in a supercritical fluid is maximal near the lower heated flange of the reactor, and decreases with approaching the upper, cooled flange. It was concluded that the separation factor of the ²³⁵U isotope in supercritical carbon dioxide can be about 1.2 ± 0.12. Експериментально досліджено просторовий перерозподіл ізотопу ²³⁵U природного урану в градієнтному полі температури по висоті реактора в надкритичному діоксиді вуглецю. Наведено схему і описаний принцип роботи реактора. Описані метод підготовки вихідних зразків із зразків гранітів, що містять природний уран, і порядок проведення екстракції. Висновок про просторовий перерозподілі ізотопів ²³⁵U в надкритичному діоксиді вуглецю заснований на аналізі гамма-спектрів екстрактів. Показано, що в надкритичному флюїді концентрація ізотопу ²³⁵U максимальна поблизу нижнього фланця реактора, що підігрівається, і зменшується з наближенням до верхнього охолоджуваного фланця. Зроблено висновок про те, що коефіцієнт поділу ізотопу ²³⁵U в надкритичному діоксиді вуглецю може становити величину близько 1.2 ± 0.12. Экспериментально исследовано пространственное перераспределение изотопа ²³⁵U природного урана в градиентном поле температуры по высоте реактора в сверхкритическом диоксиде углерода. Приведена схема и описан принцип работы реактора. Описаны метод подготовки исходных образцов из образцов гранитов, содержащих природный уран, и порядок проведения экстракции. Вывод о пространственном перераспределении изотопов ²³⁵U в сверхкритическом диоксиде углерода основан на анализе гамма-спектров экстрактов. Показано, что в сверхкритическом флюиде концентрация изотопа ²³⁵U максимальна вблизи нижнего подогреваемого фланца реактора, и уменьшается с приближением к верхнему, охлаждаемому фланцу. Сделан вывод о том, что коэффициент разделения изотопа ²³⁵U в сверхкритическом диоксиде углерода может составлять величину около 1.2 ± 0.12.